Estimation of B-Value Variation as Earthquake Precursor in Java Region with Maximum Likelihood Method. Issue 1 (1st July 2022) - Arubi, D; Zulfakriza,; Rosalia, S; Sahara, D P; Puspito, N T
Abstract: Java Island is one of the areas with a population density of 1, 171 people/km 2, which is relatively high compared to other regions in Indonesia. The tectonic setting of the Java region is affected by the interaction of tectonic plate subduction between the Indo-Australian Plate and the Eurasian Plate which moves at the rate of 67 mm/year. In addition, the presence of several active faults on Java Island also contributes to the tectonic setting. The implication of this setting is a relatively high level of potential earthquake events and some of them are destructive earthquakes. The estimation of b-value variations by using Gutenberg-Richter Equation plays an important role in estimating the occurrence of earthquakes. The aims of this study are to determine the role of spatial and temporal variations of b-value as earthquake precursors on Java Island. In this research, earthquakes analysis was carried out in the form of spatial and temporal variations of b-value from earthquake catalog data in 1900-2016 for the Java Island region. Based on the estimation of earthquake recurrence time for magnitude 6.5, 7, and 7.5, and also the analysis of spatial variation of b-value shows the areas with the potential for significant earthquakes in the west and eastern part of Java region. In addition, our result also obtains the existence of a seismic gap zone in the southern part of Central Java.